The Roles and Mechanisms of lncRNAs in Liver Fibrosis - Wang, Zhifa; Yang, Xiaoke; Gui, Siyu; Yang, Fan; Cao, Zhuo; Cheng, Rong; Xia, Xiaowei; Li, Chuanying (Frontiers in Pharmacology, 2021)
Long non-coding RNAs (lncRNAs) can potentially regulate various aspects of cellular activity including differentiation and development, metabolism, proliferation, apoptosis and activation, and its functions and mechanisms in physiological and pathological states are widely reported, thanks in large part to advances in transcriptomic and genomic research techniques and database management technologies. Liver fibrosis is typically characterized by a reversible wound healing response, often accompanied by excessive accumulation of extracellular matrix. In recent years, a series of lncRNAs have been investigated and found to act as competitive endogenous RNAs (ceRNAs) involved in several cellular-level regulatory processes that play an important role in the development of liver fibrosis, such as the activation of hepatic stellate cells (HSCs), which play an important role in the accelerated progression of liver fibrosis, and the associated alterations in cell cycle, proliferation profile have been shown to be mediated by lncRNA-Alu-mediated overexpression of the p21 transcriptional regulator (lncRNA APTR). This review aims to discuss the functions and mechanisms of lncRNAs in the development and regression of liver fibrosis and to explore the major lncRNAs involved in the signaling pathways regulating liver fibrosis, with the aim of elaborating the mechanisms mediated by lncRNA dysregulation and providing new diagnostic and therapeutic strategies for liver fibrosis.